2017
DOI: 10.1111/are.13433
|View full text |Cite
|
Sign up to set email alerts
|

First feeding of diploid and triploid yellowtail tetra Astyanax altiparanae: An initial stage for application in laboratory studies

Abstract: In this study, the aim was to establish a protocol for first feeding of diploid and triploid yellowtail tetra Astyanax altiparanae in laboratory conditions. The fry were fed with five different diets: (i) Artemia franciscana nauplii, (ii) plankton, (iii) dry food, (iv) Artemia franciscana nauplii + plankton, and (v) Artemia nauplii + plankton + dry food. Additionally, the growth and survival rates of diploid and triploid individuals were also evaluated. On day 10, the length of the fish between the treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This species can survive naturally in limiting environments, such as decreased water quality and high population density, emphasizing its potential in intensive aquaculture and aquarium systems (Bertolini et al., 2018) and has been used in basic studies and applied and in aquaculture in the laboratory (Gonçalves, Parisi, Bonelli, Sussel, & Viegas, 2014; Santos et al., 2016; Yasui et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This species can survive naturally in limiting environments, such as decreased water quality and high population density, emphasizing its potential in intensive aquaculture and aquarium systems (Bertolini et al., 2018) and has been used in basic studies and applied and in aquaculture in the laboratory (Gonçalves, Parisi, Bonelli, Sussel, & Viegas, 2014; Santos et al., 2016; Yasui et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was necessary then to understand in detail the adequate food for the yellowtail tetra. In order to fill this gap, Bertolini et al (2018) evaluated different diets and concluded that artemia and dry food optimized the growth and survival under laboratory conditions, giving them a routine for dependable growth of larvae into the juvenile stage.…”
Section: Larvae Feeding Under Laboratory Conditionsmentioning
confidence: 99%
“…Among such species, the A. altiparanae has recently been considered a model organism for basic and applied studies (Pereira-Santos et al, 2016;do Nascimento et al, , 2020ados Santos et al, 2018), especially for chromosome set manipulation, such as induction (Adamov et al, 2017;Piva et al, 2018) and rearing of triploid fish (Bertolini et al, 2018). Other studies have also shown that triploid females are sterile (do Nascimento et al, 2017a) and present increased carcass yield (do Nascimento et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%